Underwater Raman microscopy—a novel in situ tool for deep-sea microscale target studies - Liu, Qingsheng; Guo, Jinjia; Lu, Yuan; Wei, Zihao; Liu, Shuang; Wu, Lulu; Ye, Wangquan; Zheng, Ronger; Zhang, Xilin (Frontiers in Marine Science, 2022)
Microscale processes and interactions in the ocean are pervasive. They play a fundamental role in global biogeochemical cycles and have a significant impact on benthic marine ecosystems. However, our understanding of micro-scale processes and interactions appeared in the benthic environment is still very limited, particularly for the deep ocean, due to a lack of appropriate in situ observations and detection methods. To address this challenge, we have developed an in situ observation and detection system for microscopic targets suitable for the deep sea and have successfully deployed the instrument on a remotely operated vehicle to achieve in situ microscopic Raman detection of targets on the seabed over a depth of 770m. This is a combined system that integrated microscopic imaging and Raman detection techniques for in-situ observation and analysis of underwater microscale targets. The complete system consists of an electronics chamber, a detection probe and a precision external positioning device. Power supply and real-time data transmission are achieved via remotely operated vehicle (ROV) tethers. This allows researchers to operate the instrument in real-time to perform microscopic imaging capture and Raman spectroscopy acquisition of interesting targets on the seafloor. the first sea trial of the system was conducted in the South China Sea in 2020, and during the cruise, microscopic image acquisition and in-situ compositional analysis of shell fragments, seabed bedrock samples, and live sea stars were successively performed. The system has solved the key technical challenges of deep-sea microscopic imaging, demonstrated the feasibility of deep-sea microscopic imaging, and illustrated the great potential of combining Raman spectroscopy and microscopic imaging in marine research. In this paper, we present the unique design of the instrument and the deep-sea results. With further optimization, the system promises to be a versatile instrument providing a unique perspective for deep-sea geochemical and biochemical studies.